Pengembangan E-Modul Persamaan Lingkaran Kelas XI MA dengan Menggunakan Aplikasi Heyzine - Ariyani Muljo; Fenny Anggreni; Sari Maulida (Prodi Pendidikan Matematika, Fakultas Tarbiyah dan Ilmu Keguruan IAIN Langsa, 2024)
Abstract This research aims to determine the validity, practicality, and effectiveness of using the Heyzine application in teaching circular equations to 11th-grade students in senior high school. The research method employed the Four-D (Define, Design, Develop, Disseminate) development model developed by S. Thiagarajan, Dorothy Semmel, and Melvyn I. Semmel. Data collection involved documentation and questionnaires, while data analysis used a descriptive qualitative approach. The results showed that the e-module for mathematics instruction was deemed highly valid by experts and practitioners. The validity percentages of the e-module were as follows: 82.5% for subject matter experts with the criteria